2008
DOI: 10.5424/sjar/2008064-358
|View full text |Cite
|
Sign up to set email alerts
|

Weed harrowing in winter cereal under semi-arid conditions

Abstract: Five field experiments on barley and wheat have been carried out in North-Eastern Spain on the same field during the cropping seasons 1999-00 to 2003-04 to compare the effect of different harrowing adjustments on weed control, weed biomass and cereal yield. The variables considered were harrowing timing (pre-or early post-emergence), one or two passes, travelling direction, harrowing depth and speed compared with an untreated control and herbicide. Excepting year 2001, with very little weed emergence, mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
(22 reference statements)
3
11
1
Order By: Relevance
“…However, not significant differences were observed between N2 (2 passages at T1) and N3 (1 passage at T1 + 1 passage at T1+14 days) (Table 3). These results are in perfect accordance with those of Pardo et al (2008) that reported as two harrowing passes achieved a higher efficacy than one single pass and little differences were detected if the second pass was conducted the same day, across the sowing direction or 15 days later. Furthermore, Bàrberi et al (2000) observed that weeds uncontrolled by the first harrowing treatment were not controlled by the second treatment, as they were bigger then.…”
Section: Resultssupporting
confidence: 82%
“…However, not significant differences were observed between N2 (2 passages at T1) and N3 (1 passage at T1 + 1 passage at T1+14 days) (Table 3). These results are in perfect accordance with those of Pardo et al (2008) that reported as two harrowing passes achieved a higher efficacy than one single pass and little differences were detected if the second pass was conducted the same day, across the sowing direction or 15 days later. Furthermore, Bàrberi et al (2000) observed that weeds uncontrolled by the first harrowing treatment were not controlled by the second treatment, as they were bigger then.…”
Section: Resultssupporting
confidence: 82%
“…No significant differences were found between individual systems with the same type of rotation (Table 3). In addition, in this trial no yield penalties were observed in the non-chemical systems with a single harrow pass, as other authors observed in semi-arid conditions in North-Eastern Spain (Pardo et al 2008). It has been shown, in the absence of weeds, that a sowing delay reduces cereal yields in rain-fed cropping systems because the crop cannot reach the optimal or potential development in a shorter growing period (Spink et al 2005).…”
Section: Yield Datasupporting
confidence: 54%
“…Comparing our results with reports based on qualitative experimental approaches, where one or two passes with a harrow are carried out at different growth stages, is not straightforward (Dastgheib, 2004;Ausˇkalnis & Ausˇkalnien_ e , 2008;Pardo et al, 2008;Velykis et al, 2009). To describe a treatment with a cultivator by the number of passes is more or less like describing a herbicidal treatment by the amount of herbicide used without information about the active ingredient.…”
Section: Discussionmentioning
confidence: 49%
“…However, we think that selectivity is an unavoidable concept in relation to whole‐crop and intra‐row cultivation and see no alternative when decisions about aggressiveness of cultivation have to be taken. Setting and use of cultivators have to be based on the immediate crop and weed responses, because it is impossible to predict crop and weed impacts from given settings and uses of implements (Pardo et al. , 2008; Rasmussen et al.…”
Section: Discussionmentioning
confidence: 99%